Institutional and Technological Change in Japan's Economy - Hunter, Jane; Storz, Cornelia (Routledge Contemporary Japan Series, 2006)
Institutional and technological change is a highly topical subject. At the theoretical level, there is much debate in the field of institutional economics about the role of technological change in endogenous growth theory. At a practical policy level, arguments rage about how Japan and the Japanese economy should plan for the future. In this book, leading economists and economic historians of Japan examine a range of key issues concerning institutional and technological change in Japan, rigorously using discipline-based tools of analysis, and drawing important conclusions as to how the process of change in these areas actually works. In applying these ideas to Japan, the writers in this volume are focusing on an issue which is currently being much debated in the country itself, and are helping our understanding of the world's second-largest economy.